2010
DOI: 10.1525/abt.2010.72.5.12
|View full text |Cite
|
Sign up to set email alerts
|

Sectioning Clay Models Makes Anatomy & Development Tangible

Abstract: Clay models have proved to be useful teaching aids for many topics in biology that depend on three-dimensional reasoning. Students studying embryonic development struggle to mentally reconstruct the three-dimensional structure of embryos and larvae by observing prepared slides of cross-sectional slices. Students who build clay models of embryos and slice them into cross sections, however, have a much easier time interpreting the slices of real embryos and gain a deeper understanding of development in three dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Plasticine modeling and drawing are well evidenced as excellent learning tools in anatomical sciences (Motoike et al, 2009;Oh et al, 2009;Ranaweera andMontplaisir, 2009, Howell andHowell, 2010;Skinder-Meredith, 2010) and also in clinical sciences (Re, 1980;Myers et al, 2001;Claes et al, 2010;Yang et al, 2010). The kinesthetic nature of modeling and drawing provide a suitable vehicle for the phases of metacognitive learning: planning, monitoring understanding, reaction to errors and reflection, and leading ultimately to a deeper awareness of their learning.…”
Section: Introductionmentioning
confidence: 99%
“…Plasticine modeling and drawing are well evidenced as excellent learning tools in anatomical sciences (Motoike et al, 2009;Oh et al, 2009;Ranaweera andMontplaisir, 2009, Howell andHowell, 2010;Skinder-Meredith, 2010) and also in clinical sciences (Re, 1980;Myers et al, 2001;Claes et al, 2010;Yang et al, 2010). The kinesthetic nature of modeling and drawing provide a suitable vehicle for the phases of metacognitive learning: planning, monitoring understanding, reaction to errors and reflection, and leading ultimately to a deeper awareness of their learning.…”
Section: Introductionmentioning
confidence: 99%
“…As such, instructors attempt to find alternative methods to providing these hands‐on experiences that this study has shown provide valuable enhancement to learning. Others have used visuohaptic simulations (Magana and Balachandran, ), body illustration technology (Lisk et al, ), sliceable clay models (Oh et al, ; Howell and Howell, ), and animatronic robot creation (Sirinterlikci et al, ) to improve biomechanics‐related education. The findings in this study are in line with other recent research that supports the learning benefits of these other hands‐on activities.…”
Section: Discussionmentioning
confidence: 99%
“…A key concept behind these theories is that learning is constructed, with learners building upon previous knowledge (Fosnot and Perry, 2005). By introducing the appreciation of pathology to normal anatomical structures (Eftekhar et al, 2005;Manners et al, 2017) and creating cross-sections (Oh et al, 2009;Endres Howell and Endres Howell, 2010), clay is a creative medium that easily allows learners to progress their knowledge. Constructivist theories also suggest that learning is an active process, as information can be passively received An example of clay-based modeling used by the authors for teaching the basal ganglia to medical and physician associate students.…”
Section: Introductionmentioning
confidence: 99%